A war of individuals: Bloomsbury attitudes to the Great War - Atkin, Jonathan (Manchester University Press, 2002)
This book draws together for the very first time examples of the 'aesthetic pacifism' practised during the Great War by such celebrated individuals as Virginia Woolf, Siegfried Sassoon and Bertrand Russell. In addition, the book outlines the stories of those less well-known who shared the mind-set of the Bloomsbury Group when it came to facing the first 'total war'. The research for this study took five years, gathering evidence from all the major archives in Great Britain and abroad. This is the first time that such wide-ranging evidence has been placed together in order to paint a complete picture of this fascinating form of anti-war expression. Beginning with an introduction to the period and issues involved, the narrative commences with Bertrand Russell and Cambridge before moving on to cover the disparate responses of Bloomsbury, the reactions of other celebrated writers and artists before covering the more obscure participants. A themed conclusion draws the material to a close. With the Great War and the Bloomsbury Group continuing to exert a strong grip on the popular imagination, this detailed book is written with the general reader very much in mind, as well as the specialist.